2017
DOI: 10.1158/1078-0432.ccr-17-0201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Age-Related Therapy Resistance in Melanoma by Rosiglitazone-Mediated Induction of Klotho

Abstract: Purpose Aging is a poor prognostic factor for melanoma. We have shown that melanoma cells in an aged microenvironment, are more resistant to targeted therapy than identical cells in a young microenvironment. This is dependent on age-related secreted factors. Klotho is an age-related protein, whose serum levels decrease dramatically by age 40. Most studies on klotho in cancer have focused on the expression of klotho in the tumor cell. We have shown that exogenous klotho inhibits internalization and signaling of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…We therefore reasoned that BETi/MEKi could be a strategy to overcome resistance to targeted‐ and immune‐therapy. We first tested the efficacy of combining BET and MEK inhibitors in a BRAFi‐resistant Yumm1.7‐BR syngeneic mouse model with a fully competent immune system (Behera et al , ). The combination of OTX‐015 and PD901 inhibited tumor growth rate and increased animal survival (Fig A and B, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore reasoned that BETi/MEKi could be a strategy to overcome resistance to targeted‐ and immune‐therapy. We first tested the efficacy of combining BET and MEK inhibitors in a BRAFi‐resistant Yumm1.7‐BR syngeneic mouse model with a fully competent immune system (Behera et al , ). The combination of OTX‐015 and PD901 inhibited tumor growth rate and increased animal survival (Fig A and B, ).…”
Section: Resultsmentioning
confidence: 99%
“…YUMM1.7‐BRAFi‐R cells were derived from the BRAFV600E‐PTEN L/L mouse model (Dankort et al, ) and established as described (Meeth et al , ; Behera et al , ). Yumm1.7‐BRAFi‐R cells (2.5 × 10 5 ) were suspended in Matrigel and injected subcutaneously into C57Bl/6 mice (Charles River).…”
Section: Methodsmentioning
confidence: 99%
“…One of the identified suppressive mechanisms shows that the PPARγ pathway modulates the transition between epithelial and mesenchymal phenotypes of cancer cells. PPARγ activation induces reverse epithelial-mesenchymal transition, also termed MET, by directly increasing the expression of E-cadherin (39,40) and indirectly inhibiting the canonical WNT/β-catenin pathway (41)(42)(43). Consequently, cancer cells exhibit decreased invasion and migration, blocking the spreading of metastatic cells from the primary tumor to secondary metastatic organs.…”
Section: Discussionmentioning
confidence: 99%
“…After acclimation for 1 wk, weight-matched mice were randomized into 4 groups (n = 8/group) and treated s.c. with 1.5 mg/(kg/d) Tac (Prograft; Astellas Pharma, Tokyo, Japan) or 10 ml/(kg/d) vehicle (Vh; olive oil; MilliporeSigma, Billerica, MA, USA), with or without recombinant mouse Klotho (rKlotho; 10 mg/kg), once every 2 d by intraperitoneal injection for 4 wk. rKlotho protein, which contains the entire extracellular region (Ala35-Lys982), without the transmembrane domain and intracellular domain, was purchased from R&D Systems (Minneapolis, MN, USA), and its biologic activity has been extensively characterized by the manufacturer and in previous reports (11,(16)(17)(18)(19)(20)(21). Administration routes and drug doses were selected based on previous studies that showed a significant renal protective effect in a Tac-induced mouse model of renal injury (11).…”
Section: Tac-induced Renal Injury Mouse Modelmentioning
confidence: 99%